A new element involved in the regulation of tetralin degradation genes in Sphingopyxis granuli strain TFA - García-Romero, Inmaculada; Santero, Eduardo; Floriano, Belén (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2017)
Motivation: Sphingopyxis granuli strain TFA is a gram-negative bacterium able to grow on the organic solvent tetralin as the sole carbon and energy source. Tetralin is a bicyclic molecule, composed of an aromatic and an alicyclic moiety, which is toxic to bacterial cells as it makes the membrane permeable for ions (protons) and inhibits the respiratory enzymes (Sikkema et al., 1992). In our lab, the metabolic pathway and the specific regulation of genes involved on tetralin degradation (thn genes) has been deeply characterized (López-Sánchez et al., 2010 and references therein, Rivas-Marín et al., 2016 and references therein). Regarding the regulation, it is known that structural thn genes are induced in the presence of tetralin by ThnR, a LysR-like transcriptional regulator, and ThnY, a ThnR co-activator. Besides, the expression of thn genes is under carbon catabolite repression (CCR) by preferential carbon sources, such as β-hydroxybutyrate (β-HB) or sebacic acid. However, not very much is known about the regulatory elements involved in this repression. Synthesis of the carbon storage granule PHB is indirectly involved in CCR on thn genes. Methods: Comparison of the global gene expression in tetralin- and β-HB-grown cells revealed the presence of a small non-coding RNA (sRNA), annotated by Infernal Software 1.1, preferentially expressed in β-HB. Northern Blot analysis and β-galactosidase assays of a chromosomally integrated suhB::lacZ transcriptional fusion confirmed the differential expression of this sRNA. Expression of thn genes under CCR conditions in a mutant lacking the sRNA was evaluated using a chromosomally integrated thnC::lacZ translational fusion. Furthermore, putative targets of the sRNA were detected in vitro by IntaRNA software and the predicted interaction was experimentally validated by RNA-RNA EMSA. Results: A differentially expressed sRNA has been identified in TFA as belonging to the Rfam family RF00519 (SuhB) (García-Romero et al., 2016). It is a highly conserved sRNA in α-proteobacteria. Under CCR conditions, thn genes are partially de-repressed in a mutant lacking SuhB. Furthermore, the 5' UTR of thnR mRNA has been identified in silico as a target of SuhB. Direct interaction of SuhB at the thnR ribosomal binding site has been demonstrated. The high level of ThnR in the SuhB mutant indicates a negative role of SuhB on ThnR translation. Conclusions: The available data so far indicate that SuhB is one of the elements involved in CCR of thn genes in Sphingopyxis granuli strain TFA, by blocking the translation of the regulator ThnR.